A simple and portable method for on-line texture measurement of Italian "Speck Alto Adige". (August 2022) - Bianchi, Flavia; Gamper, Gerhard; Lozano, Lidia; Simoncini, Nicoletta; Virgili, Roberta; Spada, Lukas; Venir, Elena
Abstract: Texture is a relevant parameter for the assessment of cured ham's quality. In this study a rapid on-line instrumental technique for the measurement of the texture of pieces of cured smoked ham intended for sale as "Speck Alto Adige" PGI was developed. Speck samples were subjected to a compression test using a portable Shore A tester, and instrumental data were compared with conventional texture analyses (texture profile analysis and stress relaxation test) and with sensory evaluations. First, a hardness range in which a threshold value could be identified for the eligibility of 120 speck samples for the "Speck Alto Adige" PGI indication was established; afterwards, a Shore A hardness threshold value of 48 was defined based on measurements of more than 1000 samples. These findings may help manufacturers to determine the textural properties of Speck, based on a simple and rapid instrumental analysis. Graphical abstract: Unlabelled Image